2018
DOI: 10.1017/s0033291718003628
|View full text |Cite
|
Sign up to set email alerts
|

Visual attention in adults with attention-deficit/hyperactivity disorder before and after stimulant treatment

Abstract: BackgroundAttention-deficit/hyperactivity disorder (ADHD) is a neurodevelopmental disorder which frequently persists into adulthood. The primary goal of the current study was to (a) investigate attentional functions of stimulant medication-naïve adults with ADHD, and (b) investigate the effects of 6 weeks of methylphenidate treatment on these functions.MethodsThe study was a prospective, non-randomized, non-blinded, 6-week follow-up design with 42 stimulant medication-naïve adult patients with ADHD, and 42 age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Maruta et al (2017) reported that patients with ADHD performed more poorly than controls on visual tracking and simple reaction time tasks, even when on medication. Low et al (2019) also reported significant slower processing speed levels for individuals with ADHD, but those differences were reduced to trend level after excluding a subgroup of ADHD patients positive for dyslexia. Separately, for the trail Making Test part A, Tatar and Cansiz (2019) reported no group differences on Trail A time (p > 0.05).…”
Section: Attention and Processing Speedmentioning
confidence: 91%
“…Maruta et al (2017) reported that patients with ADHD performed more poorly than controls on visual tracking and simple reaction time tasks, even when on medication. Low et al (2019) also reported significant slower processing speed levels for individuals with ADHD, but those differences were reduced to trend level after excluding a subgroup of ADHD patients positive for dyslexia. Separately, for the trail Making Test part A, Tatar and Cansiz (2019) reported no group differences on Trail A time (p > 0.05).…”
Section: Attention and Processing Speedmentioning
confidence: 91%
“…Therefore, lower GMV of the identified clusters in never-medicated patients with ADHD may exclude one alternative explanation that lower GMV was caused secondarily by medication, while comparable GMV between medicated patients and TD controls suggests medication may have a remedial effect for ADHD on brain structure, which provides a possible neuroanatomical basis for the behavioral improvement in visual attention by stimulant treatment for ADHD (68).…”
Section: Medication Effectsmentioning
confidence: 98%
“…The characteristics of individuals with ADHD include inattention, hyperactivity and impulsivity [ 4 ]. Many children with ADHD continue to show symptoms in adolescence and adulthood, frequently struggling with various aspects of their lives [ 5 , 6 ]. ADHD in adults has historically been underdiagnosed and has received less research attention than childhood ADHD [ 7 ].…”
Section: Introductionmentioning
confidence: 99%